Primera biblioteca de llamadas de ecolocalización de murciélagos del Ecuador - Rivera-Parra, Pamela; Burneo, Santiago F. (THERYA, 2013)
Echolocation calls in bats have several functions including orientation and searching for prey both in the approach and terminal phases of prey capture. These searching calls are species specific and can be used for identification to the species level. The research of echolocation calls has a long history in studies of the Chiroptera and has recently has been enhanced through digital technology. Although there is an extensive literature on echolocation related matters, there are only a limited number of calls in echolocation call libraries. Scientists in the Mammal Collection of the Zoology Museum of the Pontifical Catholic University of Ecuador began working with echolocation calls in 2010. The Museum maintains a web site, FaunaWeb, with a section, MammaliaWeb-Ecuador, which has a library of bat echolocation calls. As of November 2012, there were recordings of 28 species of bats in the library. We are expanding this call library as calls with reliable species identification become available. Key words: bats, echolocation, Ecuador, library, search calls.